2014
DOI: 10.1590/1982-0194201400088
|View full text |Cite
|
Sign up to set email alerts
|

Riscos ocupacionais e adoecimento de trabalhadores em saúde mental

Abstract: Objective: To analyze the association between illness and occupational risks among mental health workers. Methods: An epidemiological cross-sectional study was conducted with 163 professionals who were members of a multidisciplinary mental health team at a psychiatric hospital, split into two groups: those who had and those who had not taken medical leaves of absence. Data were collected using a questionnaire examining the studied variables and by accessing records of medical leaves of absence. Results: The id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
3
0
11
Order By: Relevance
“…Research in a psychiatric hospital showed that, among ergonomic risks at workplace, the monotony/repetitiveness of work is one of the factors most reported by workers 17 . This situation may be related to the experience that nursing workers have in the mental health field of nursing, which consists of repetitive and mechanical movements and is full of rules, routines, norms and based on performing tasks without feelings 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Research in a psychiatric hospital showed that, among ergonomic risks at workplace, the monotony/repetitiveness of work is one of the factors most reported by workers 17 . This situation may be related to the experience that nursing workers have in the mental health field of nursing, which consists of repetitive and mechanical movements and is full of rules, routines, norms and based on performing tasks without feelings 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Esse mesmo resultado foi encontrado em duas pesquisas realizadas sobre risco ocupacional em um hospital psiquiátrico de Teresina e no SAMU da região metropolitana de Natal -RN, no qual o ruído foi o risco físico (47,6%) mais prevalente (1)(2) . A surdez é um dos distúrbios mais evidentes nos indivíduos expostos ao som de sirene de ambulância.…”
Section: Discussionunclassified
“…Simultaneamente, surgem novos tipos de Doenças Profissionais, oriundas de riscos emergentes ocasionados por condições ergonômicas deficientes, exposição à radiação eletromagnética e riscos psicossociais (1) .…”
Section: Introductionunclassified
“…A maior parte dos artigos traz, como ponto inicial dos seus resultados, uma caracterização do perfil da população estudada na pesquisa 8,9,10,11 . , os riscos ocupacionais são situações de trabalho que podem romper o equilíbrio físico, mental e social das pessoas trazendo para as mesmas repercussões, e não somente aquelas que originem acidentes ou enfermidades.…”
Section: Categoria 1: Perfil Epidemiológico Da População Estudadaunclassified